Pengembangan E-LKPD Berbasis Pembelajaran Berdiferensiasi Materi Zat Dan Perubahannya Untuk Meningkatkan Hasil Belajar Peserta Didik - Maulida Zahra; Syubhan Annur; Sauqina (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This research focuses on developing an e-LKPD (electronic Student Worksheet) based on differentiated learning for the topic of matter and its changes, aimed at improving student learning outcomes. The objectives are to assess its validity, practicality, and effectiveness. The study uses a Research and Development (R&D) method with a modified 4D model (Define, Design, Develop) and involves class VIIC students at SMP Negeri 13 Banjarmasin. Data were collected through expert validation sheets, student response questionnaires, and pre-test–post-test evaluations. The e-LKPD achieved a validity score of 0.8, categorized as very valid. Student response questionnaires showed a practicality score of 97.1%, indicating the e-LKPD is highly practical. Effectiveness was measured through N-gain analysis, with an average score of 0.8, categorized as high. These results demonstrate that the developed e-LKPD is a valid, practical, and effective tool for improving students' understanding of the topic and enhancing their overall learning outcomes.